A brief survey of software architecture concepts and service oriented architecture - Valipour, Mohammad Hadi; Amirzafari, Bavar; Maleki, Khashayar Niki; Daneshpour, Negin (2009 2nd IEEE International Conference on Computer Science and Information Technology, 2009)
A critical issue in the design and construction of any complex software system is its architecture. Software architecture as an important column of software development process has various methods and roadmaps that all of them have some common principles and inception. Architecture-based approaches have been promoted as a means of controlling the complexity of systems construction and evolution. In this paper we try to describe basics and main structure of software architecture with a conceptual view to this issue. First, architecture definitions are presented. Finally service-oriented architecture (SOA) as one of useful choices for software architecture to develop web software and systems is glossed in a survey.